KESIAPAN KERJA MAHASISWA AKUNTANSI DI ERA DIGITAL: CUKUPKAH HANYA HARD SKILLS? - Naufal Afif; Azizah Hasna Arifin (Faculty of Economics and Business, Universitas Warmadewa, 2022)
Demands for college graduates are increasing. Traditionally, the academic ability has spearheaded the success of college graduates to get a job. However, the current trend of employers increasingly wants skills and other attributes to support academic skills, as well as for accounting graduates. World economic forum report on expertise needed in 2020 and the development of the 4.0 industrial revolution requires accounting graduates to have skills and attributes in addition to academic abilities. The purpose of this study is to examine the effect of soft skills provided by tertiary institutions and the spiritual intelligence of individuals on the readiness of accounting students to work. Using Covariance-based Structural Equation Model (CB-SEM), this study analyses the results of a survey distributed to 371 accounting students in Indonesia. The result, based on structural model testing shows that soft skills provided by higher education and spiritual intelligence significantly and positively affect the work readiness of accounting students. The results of the research provide input for universities to continue to develop learning about soft skills to students so that graduates can compete in the world of work. This study also provides empirical evidence that the readiness of accounting students is also influenced by the attribute inherent in human beings, namely spiritual intelligence.